The working status and deformation risk of membrane walls affected by the arrangement of burners in the arch-fired boiler. (25th November 2020) - Li, Lian; Zhou, Qulan; Wen, Du; Li, Na; Yao, Yashu; Ao, Yunjin
Graphical abstract: In this paper, experiments were conducted in the laboratory-scaled arch-fired boiler, exploring the correlations of the working status on membrane walls and the arrangement of burners. The influence mechanism and impact range of the burners on the membrane walls were experimentally determined. The flameout of burners enhanced the tearing risk of the local membrane walls, which is consistent with the tearing track in the prototype boiler. The volumetric thermal load of the boiler and the impact range of burners played important roles in the combined action of multiple burners, offering reference to the design and operation of arch-fired boilers. Highlights: The mechanism and impact range of burners on membrane walls were found. Flameout of burners increases tearing risk of membrane walls via tension stress. The boundary effect of side walls results in the position difference of burners. Correlation of membrane wall status and volumetric thermal load were confirmed. The strong impact range of burners affects the uniformity of working parameters. Abstract: The thermal deformation of membrane walls is a severe safety issue in the arch-fired boilers, which is closely related to the combustion and flame inside the furnace. In this paper, various combustion schemes were conducted on a laboratory-scaled arch-fired boiler, exploring the correlations between the working status on membrane walls and the arrangement of burners. The influence mechanisms of the burners on the membrane walls were experimentally determined, with strong impact regions found on the front/rear wall in a relative wide of 0.6. The asymmetric combustion obtained in the furnace increased the temperature and strain/stress on the front wall with greater deformation risk, which should be avoided in the practical operation. The flameout of burners dramatically changed the local temperature and enhances the tearing risk of membrane walls with tension stress, which is consistent with the tearing track in the prototype boiler. Great correlations between the operation parameters ( T g, T w, T c, ε 1 and σ 1 ) and the and volumetric thermal load ( P v ) were experimentally determined and considered applicable to the prototype boiler. While the impact range of burners helps estimating the uniformity of temperature and strain/stress on membrane walls, providing reference to the design and operation of similar boilers.